Case Study Of Damansara Uptown Car Parks Sdn. Bhd. - K. Pichai, Sivakumar (2008)
This case study seeks to answer some of the mind boggling questions as to why the company was unable to make brekthrough thus far and provide possible solutions that could be implemented. The study begins by unraveling the trend of outsourcing in general. We also examined the industry standards, norms and practices generally as well as within Malaysian context.